2005
DOI: 10.2141/jpsa.42.39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Artificial Insemination on the Structure and Function of Oviducal Sperm Storage Tubules in Hens

Abstract: The goal of this study was to determine the mechanism by which the fertility was declined by repeated artificial insemination (AI) in laying hens. The structures of sperm storage tubules (SST) and lymphocytes population in the uterovaginal junction (UVJ) of Rhode Island Red hens showing a declined fertility after repeated AI with Tosa-jidori semen and of virgin hens were examined histologically in experiment +. Then, the sperm storage abilities of those hens were examined in experiment ,. In experiment +, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The large inner diameter of the SSTs in old hens resulted in a wider lumen of the SSTs ( Figure 1 ), which was associated with swelling of the SST structure, which might explain the declined sperm reservoir within the SSTs in old hens. This was also reported by Das et al [ 17 ], who suggested the destruction of the SSTs, including swelling, in older hens. This phenomenon might explain why older hens with long-term use are more susceptible to inflammation reactions caused by AI, resulting in SST destruction [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The large inner diameter of the SSTs in old hens resulted in a wider lumen of the SSTs ( Figure 1 ), which was associated with swelling of the SST structure, which might explain the declined sperm reservoir within the SSTs in old hens. This was also reported by Das et al [ 17 ], who suggested the destruction of the SSTs, including swelling, in older hens. This phenomenon might explain why older hens with long-term use are more susceptible to inflammation reactions caused by AI, resulting in SST destruction [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 82%
“…The histological examination of UVJ tissues was carried out as described previously [ 17 ]. Briefly, the UVJ tissues were identified and dissected under a stereomicroscope, where they appeared as a distinct band of thin and convoluted folds [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…One factor that is essential for sperm survival in storage is the suppression of the female immune response, which if triggered can have highly detrimental effects on sperm. In domestic fowl, repeated artificial inseminations were associated with a complete lack of stored sperm and a 57% decrease in fertility [164,165]. This has been attributed to an influx of lymphocytes and antigen-presenting cells into SSTs that probably impair sperm survivability, but also prevent sperm from entering storage [164].…”
Section: Failure To Maintain and Transport Sperm 341 Sperm Storage Tubule Functionmentioning
confidence: 99%
“…In domestic fowl, repeated artificial inseminations were associated with a complete lack of stored sperm and a 57% decrease in fertility [164,165]. This has been attributed to an influx of lymphocytes and antigen-presenting cells into SSTs that probably impair sperm survivability, but also prevent sperm from entering storage [164]. A significant decrease in the expression of oestrogen receptors in the sperm storage tubules was also observed following infection, probably impairing the hormonal control of sperm storage tubule function [165].…”
Section: Failure To Maintain and Transport Sperm 341 Sperm Storage Tubule Functionmentioning
confidence: 99%
“…The destruction of SSTs, including swelling in older hens brought about by long-term use for artificial insemination (AI), could be the reason for the decreased ability of SSTs to preserve sperm [ 14 ]; however, this phenomenon has been observed even in virgin old hens [ 6 ]. Therefore, the reason for declining fertility in old hens is speculated to be a higher sperm release rate from the SSTs of old hens compared to those of younger hens, as mentioned in unpublished data by Brillard [ 7 ].…”
Section: Introductionmentioning
confidence: 99%